Inflation and Corruption Relationship: Evidence from Panel Data in Developed and Developing Countries - Akça, Haşim; Ata, Ahmet Yılmaz; Karaca, Coşkun (International Journal of Economics and Financial Issues, 2012)
Corruption, which is defined as the illegal and benefit-oriented usage of public power, is a fact that has an impact on the macro-economic performance of economy in the scope of cause and effect. Within this framework, there is a strong cause and effect interaction between inflation, an important economic parameter, and corruption. Inflation is defined as not only a financial factor results in corruption but also an economic problem results from corruption. With this particular study, the relationship between inflation and corruption was tried to be tested one-way. In this context, the impact of inflation, growth, trade gap, the quality of legislation, the efficacy of government, political stability and responsibility variables on corruption was tested through panel data method concerning to the 2002-2010 period of totally 97 countries from three different income-level group. It was found as a result of the empirical data that the inflation has a statistically significant and positive effect on corruption in all these 97 countries from three different income-level groups. Keywords: Inflation; Corruption; Panel Data JEL Classifications: D02; D40; D72; D73; D82